Optimization of Machining Parameters for Turning of Al6061 Using Robust Design Principle to Minimize the Surface Roughness. (2016) - Deepak, D.; Rajendra, B.
Abstract: The present work aims at optimization of the process parameter such as cutting speed, depth of cut and feed rate on surface roughness produced on the machined component. Analysis is carried out using Taguchi robust design principles. From the analysis, feed rate is found to be the most influential process parameters which influence the surface roughness followed by cutting speed and depth of cut. Increase in feed rate and depth of cut is found to increase the surface roughness.